Taxonomic studies of Myrcia (Myrciinae, Myrtaceae) in Brazil: morphological novelties, circumscriptions, and new records for the Amazon - Rosário, Alessandro Silva; Baumgratz, José Fernando; Secco, Ricardo (Iheringia, Série Botânica., 2017)
Based on recent studies on Myrtaceae in the Brazilian Amazon, we present an update of the morphological circumscription of Myrcia, including eight new occurrences of the genus in Pará State, three of which represent new records for the Amazon region. Comments are provided on the diagnostic features and taxonomic affi  nities of each species, their geographic distributions, and their preferred environments of occurrence. Recommendations for updating the list of Brazilian Myrtaceae species are presented.